PENGGUNAAN MODEL PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS X IPA 1 SMA NEGERI 15 KOTA TAKENGON TAHUN PELAJARAN 2018-2019 - Wira Yanti (Universitas Islam Negeri Ar-Raniry, 2019)
This study aims to improve the teaching process and learning outcomes with the application of Direct Instruction model in class X IPA 1 at SMAN 15 Takengon. This research is Classroom Action Research with descriptive method that uses two cycles, each cycle consisting of four stages: planning, implementation, observation, and reflection. Subjects were researchers as a biology teacher and the entire class of students of SMA 15 X IPA 1 SMAN 15 Takengon that consists of 30 boys and 18 girls. Data collection techniques were observation and tests, while the research instrument consisted of observation sheets and test sheets. Observation sheet is used to describe teaching and learning activities and test sheets is used to describe the results of learning outcomes in the form of multiple choice questions. The teachers’ activities in cycle I obtained an average score of 17 (good) while in cycle II increased to 21 (excellent). The students learning activities in cycle I earned an average score of 16 (enough), while in cycle II increased to 21 (excellent). In cycle I the average value of the grade is 66.67 with the classical grade not completed (43.33 %), while in cycle II the average value increased to be 85.33 with percentage of classical grade 80 % (complete). It was concluded that the direct instructional model can improve the teachers and students learning activities while also improve students learning outcomes in class X IPA 1 SMA 15 Takengon.